Radioiodination of monoclonal antibodies, proteins and peptides for diagnosis and therapy - Behr, Th. M.; Gotthardt, M.; Becker, W.; Béhé, M. (Nuklearmedizin - NuclearMedicine, 2002)
Simple and reliable methodologies for radioiodination of proteins and peptides are described. The labeling systems are easy to assemble, capable of radioiodinating any protein or, with slight modifications, also peptide (molecular mass 1000-300,000) from kBq to GBq levels of activity for use in diagnosis and/or therapy. Furthermore, the procedures are feasible in any nuclear medicine department. Gigabecquerel amounts of activity can be handled safely. The most favored iodination methodology relies on the Iodogen system, a mild oxidating agent without reducing agents. Thus, protein degradation is minimized. Labeling yields are between 60 and 90%, and immunoreactivities remain ≥ 85%. Other radioiodination methods (chloramine-T, Bolton-Hunter) are described and briefly discussed.
Keywords: Radioimmunotherapy; radioiodination